The function of immunomodulation and biomaterials for scaffold in the process of bone defect repair: A review - Dong, Changchao; Tan, Gang; Zhang, Guangyan; Lin, Wei; Wang, Guanglin (Frontiers in Bioengineering and Biotechnology, 2023)
Bone provides a solid barrier for the origin and development of immune cells in the bone marrow. The process of bone regeneration involves the interaction of the skeletal, blood, and immune systems. At the same time, immune cells secrete factors to feedback on the remodeling of the skeletal system. Pathological or traumatic injury of bone tissue involves changes in blood supply, cell behavior, and cytokine expression. Immune cells and their factors play an essential role in repairing foreign bodies in bone injury or implantation of biomaterials, the clearance of dead cells, and the regeneration of bone tissue. This article reviews the bone regeneration application of the bone tissue repair micro-environment in bone cells and immune cells in the bone marrow and the interaction of materials and immune cells.